7(4y-7)-(2y+7)=

Simple and best practice solution for 7(4y-7)-(2y+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(4y-7)-(2y+7)= equation:


Simplifying
7(4y + -7) + -1(2y + 7) = 0

Reorder the terms:
7(-7 + 4y) + -1(2y + 7) = 0
(-7 * 7 + 4y * 7) + -1(2y + 7) = 0
(-49 + 28y) + -1(2y + 7) = 0

Reorder the terms:
-49 + 28y + -1(7 + 2y) = 0
-49 + 28y + (7 * -1 + 2y * -1) = 0
-49 + 28y + (-7 + -2y) = 0

Reorder the terms:
-49 + -7 + 28y + -2y = 0

Combine like terms: -49 + -7 = -56
-56 + 28y + -2y = 0

Combine like terms: 28y + -2y = 26y
-56 + 26y = 0

Solving
-56 + 26y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '56' to each side of the equation.
-56 + 56 + 26y = 0 + 56

Combine like terms: -56 + 56 = 0
0 + 26y = 0 + 56
26y = 0 + 56

Combine like terms: 0 + 56 = 56
26y = 56

Divide each side by '26'.
y = 2.153846154

Simplifying
y = 2.153846154

See similar equations:

| 3-6(5x+6)=177 | | 7+2v=23 | | -6(3r+6)=-90 | | -8+8(a-5)= | | 4x+10yz-3=0 | | -5(3x+3)+4=-71 | | 4(1+4k)-3= | | 5((1/2)-3) | | (12x+66)+(2x+20)=9 | | 2(3f+1)= | | -6(1+6x)-1= | | 4n+3(6n-1)=-135 | | 5(1/2-3) | | 2x-17=7x+12 | | 10x+9=7x+8 | | 8p+4=7+7p | | cx+b=5(x-c) | | 4-(3n-3)= | | -14y+28+6x=-44 | | -5*a+(-5*b)=3 | | 32+0.25y=50 | | log(x)=-22.7 | | 1/2•32= | | -268=12(x)-4 | | 8b+8(1-8b)= | | -268=4-12(x) | | 5/9x3/15 | | F(3)=1/2•32 | | 2x+-9(2)=9 | | 4-12(x)=-268 | | 2x+-9(0)=9 | | 9(12/7)+7= |

Equations solver categories